Unravelling the Interconnection of Stock Markets during Global Financial Crisis and Global Pandemic Crisis: The European and Asian Perspectives - Sekhar, D.; Joseph, B. (Department of Economics, University of Colombo, Sri Lanka., 2025)
Equity markets are seen as indicators of economic health because stock prices reflect the collective information and expectations of various market participants. Even though there have been several stressful events in the global stock markets since the beginning of the 21st century, the two glaring distortions are the Global Financial Crisis (GFC) of 2007-2009 and the COVID-19 pandemic (Global Pandemic Crisis - GPC). Diversifying portfolios internationally can provide a more efficient frontier for investors than investing domestically but increased financial integration among stock markets reduces the diversification benefits. During crises, the stock markets deviate from the long-run relationships and patterns. Thus, it is significant for the investors and portfolio managers to understand the interconnections among stock markets within the region and the extent of impact during crises. The European markets exhibited cointegration only during GFC, whereas the Asian stock markets had a co-movement during the GPC and GFC. The study offers insights for policymakers in crisis affected nations in formulating plans to boost stock market performance should.
Keywords: Global Financial Crisis; Global Pandemic Crisis; Impulse Response Function; Economic Integration; Stock Market Integration; Johansen Cointegration Method